2016
DOI: 10.1071/py14180
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the ability of Australian primary healthcare services to respond to health inequity

Abstract: Equity of access and reducing health inequities are key objectives of comprehensive primary health care. However, the supports required to target equity are fragile and vulnerable to changes in the fiscal and political environment. Six Australian primary healthcare services, five in South Australia and one in the Northern Territory, were followed over 5 years (2009–2013) of considerable change. Fifty-five interviews were conducted with service managers, staff, regional health executives and health department r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Data were drawn from a larger study on comprehensive PHC that partnered with five South Australian services and Congress 4,21–23 . The six PHC services were selected to maximise diversity and because they had existing relationships with the research team that would make participation in a five‐year research project (2009–2014) feasible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were drawn from a larger study on comprehensive PHC that partnered with five South Australian services and Congress 4,21–23 . The six PHC services were selected to maximise diversity and because they had existing relationships with the research team that would make participation in a five‐year research project (2009–2014) feasible.…”
Section: Methodsmentioning
confidence: 99%
“…b) Congress staff interviews . There were two rounds of staff interviews, one in 2009–2010, including 14 interviews with Congress staff and board members 25 and one in 2013–2014, including 15 interviews with Congress staff and board members 22 . The first round explored implementation of comprehensive PHC principles at the service, while the second round focused on how this had changed in the intervening four years.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the interviews have been reported elsewhere. 14 In 2013, a total of 63 interviews were conducted with service practitioners and managers in the seven PHC sites, and regional and central health executives.…”
Section: Methodsmentioning
confidence: 99%
“…Our review found a number of studies showing that community-controlled CPHC services deliver health and access benefits for Aboriginal people (e.g. Parker et al 2012;Kelaher et al 2014;Bath and Wakerman 2015;Freeman et al 2016). Collaborative models of care between ACCHSs, PHC and acute care services also have been shown to improve service access and health outcomes for Aboriginal people in a remote setting (Reeve, et al 2015).…”
Section: Phc For Aboriginal and Torres Strait Islander Peoplesmentioning
confidence: 95%